Pressing Challenges for Educators Committed to Citizenship and Human Rights Education through Model United Nations - Penhos, Matías (2025)
Model United Nations (MUN) role-playing simulations serve as an exceptional tool for applying pedagogical principles rooted in global citizenship and human rights education. When teachers undertake pedagogical guidance to various high school student groups, they are aware that the process culminating in the UN staging is fraught with unforeseen occurrences, despite thorough planning. The possibilities of sustaining non-formal education activities in the medium term largely depends on the commitment and unwavering dedication of the teaching staff. This article focuses on that commitment. Rooted in a socio-community framework with careful attention to territorial articulation, collective efforts were made to meet the expectations of the student groups involved. The collaborative initiative took place at Secondary School No. 5 in Ezpeleta, Buenos Aires Province, Argentina, which is one of the most representative venues for the Model United Nations of the National University of Quilmes (MONUUNQ). Throughout and after the COVID-19 pandemic, an extraordinary capacity for contextual adaptation enabled the sustaining of on-site workshops, training sessions, and role-playing simulations. Particular attention was focused on enhancing the pedagogical-didactic strategies of the institution's educators, who had highly heterogeneous profiles in relation to the practice of MUN. The records and testimonies of the student participants enable us to reinterpret, in a highly positive manner, the experiences and practices that have had a significant impact on the school.